Synthesis of TiN-Si3N4 composites from rutile and quartz by carbothermal reduction nitridation - Chen Kai; Huang Zhaohui; Fang Minghao; Liu Yan-Gai (Science of Sintering, 2012)
TiN-Si3N4 composite powders were prepared by carbothermal reduction nitridation using rutile and quartz as raw materials. The influence of temperature and carbon addition on the phase evolution and microstructure of the products were investigated. The equilibrium phase diagram of Si-C-N-O and Ti-C-N-O system at different temperatures under 0.2 MPa nitrogen pressure was drew. The results show that the optimum parameters for synthesizing TiN-Si3N4 by carbothermal reduction nitridation process are carbon addition of stoichiometric content, temperature of 1873 K for 4 h and nitrogen pressure of 0.2 MPa. The produced TiN-Si3N4 in this experiment exist in granular and hexagonal columnar shape, and the average particle size of the synthesized powders is 2 ~ 10 μm.